Kajian Filsafat Ilmu Terhadap Undang-Undang Coorporate Social Responsibility (CSR) (Kasus CSR Perusahaan Batubara di Kabupaten Kutai Kartanegara Kalimantan Timur) - Ilmansyah dan Florentinus Sudiran (DEDIKASI : Jurnal Ilmiah Sosial, Hukum, Budaya, 2016)
This research was held in Kutai Kertanegara Regency in 2014. The aim of it is to know how the Corporate Social Responsibility (CSR) of the companies operating in this regency has been realized. One of the aids in CSR is the care of the company to develop and empower the society. It is hoped that this program can support and empower to create the sustainable activity. A company has to the care of the environment as a principle by reducing the pollution, the destruction of the area. The result of the research is that the companies must support the society seriously arround their area. The suggestions are make some efforts to minimize the emition, to use the renewable energy, to manage the waste and pollution